Evidence for mirror self-recognition in beluga whales (Delphinapterus leucas) - Alexander Mildener; Diana Buchman; Sonia Ragir; Diana Reiss (PLoS ONE, 2026)
Tests of mirror self-recognition (MSR) have provided behavioral evidence of a high level of self-awareness in humans, chimpanzees, bonobos, orangutans, gorillas, bottlenose dolphins, Asian elephants, magpies, and to some extent in the cleaner wrasse. We conducted the standard mirror test with a social group of four beluga whales ( Delphinapterus leucas), one subadult and three adult females, housed together at the New York Aquarium of the Wildlife Conservation Society. We exposed the whales to a two-way plexiglass mirror and a transparent control surface during baseline and post-mirror sessions and recorded and analyzed their behavioral responses in the three conditions. Two of the four whales, the subadult and her mother, exhibited a rich suite of self-directed behaviors at the mirror and subsequent mark and control sham-mark tests were conducted with both whales. The adult female showed mark-directed behavior at the mirror and passed one of the initial mark tests in a series of tests given. The self-directed behaviors exhibited by both whales and mark directed behavior by the adult female provides evidence for the capacity of MSR in the beluga whale.